Judging Mohammed : juvenile delinquency, immigration, and exclusion at the Paris Palace of Justice - Terrio, Susan J. (Susan Jane), 1950- (Stanford, Calif. : Stanford University Press, 2009)
This groundbreaking study goes inside France's juvenile court system and follows young people, largely of foreign ancestry, from arrest to court trials, revealing an alarming shift in the nation's approach to its youth offenders.
Are they all delinquents? -- The French criminal justice system -- New savages in the city? historical and contemporary representations of juvenile delinquency -- Justice for minors : a minor justice? -- Getting arrested and going to court -- Rendering justice in chambers -- Judging delinquents in the juvenile court -- New barbarians at the gates of Paris? : the problem of undocumented minors.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Juvenile justice, Administration of -- France -- Paris; Juvenile delinquency -- France -- Paris; Juvenile courts -- France -- Paris; Minority youth -- France -- Paris; Children of immigrants -- France -- Paris; Electronic books; Délinquance juvénile -- France -- Paris; Tribunaux pour enfants et adolescents -- France -- Paris; Jeunesse issue des minorités -- France -- Paris; Enfants d'immigrants -- France -- Paris; Livres numériques.; e-books.; SOCIAL SCIENCE -- Criminology; Children of immigrants; Juvenile courts; Juvenile delinquency; Juvenile justice, Administration of; Minority youth; France -- Paris; Jugendgericht; Jugendkriminalität; Migrationshintergrund; Rechtsprechung; Paris